Case Report: Complex Regional Pain Syndrome Involving the Head and Face After Severe Malignant Otitis Media and Mastoiditis - Hunter Collins (Cephalalgia Reports)
Background Complex regional pain syndrome (CRPS) is a rare condition characterized by intense chronic pain, vascular changes, swelling, and trophic changes leading to significant morbidity. It is often related to crush/mechanical injury or surgery and most commonly affects the limbs. There have only been a few rare documented cases affecting the head and face, and more scarce are CRPS cases of the head and face unrelated to trauma. Case We report a 79-year-old woman referred to Neurology after three months of severe, persistent left-sided head and face pain associated with discrete episodic swelling and localized autonomic symptoms, skin and hair changes in the affected area, following severe otitis media complicated by mastoiditis. Her history and neurologic exam did not meet a categorical diagnosis based on criteria in The International Classification of Headache Disorders-3rd edition and International Classification of Orofacial Pain, 1st edition but her symptoms and signs met the Budapest Criteria (BC) for a diagnosis of CRPS of the head and face. The patient had been on carbamazepine with only marginal benefit. After the initial Neurology evaluation, she started duloxetine and was referred for mirror visual feedback therapy. During an acute attack, she had a very good response to a sphenopalatine ganglion block and compounded intranasal and topical lidocaine-ketamine preparations were adjunctively added. Eleven months after initial symptom onset, she reported significant symptomatic improvement with markedly decreased disability and return to her premorbid quality of life. Conclusion Complex regional pain syndrome is difficult to recognize, there are no diagnostic tests, there is no definitive cure and management is symptomatic. Early identification and treatment may prevent significant morbidity and we recommend review and classification of such cases using the BC.